Synthesis of bio-lubricant by esterification of pelargonic acid with 2-ethylhexanol over amberlyst 36 - Teck Huai, Ng (2015)
In recent years, the demand of bio-lubricant has greatly increased due to the environmental and sustainability issue created by mineral oil based lubricant. This study addresses the issue of low oxidative stability of the current bio lubricant by substituting one of the raw materials with saturated base oil. Homogeneous catalyst employed in the current production process is also replaced by Amberlyst 36, a heterogeneous catalyst to eliminate the complications in product separation and the occurrence of side reaction. This work presents the synthesis of bio-lubricant, 2-ethylhexyl pelargonate through the esterification of pelargonic acid and 2-ethylhexanol. In this study, a batch reactor completed with dean stark apparatus was used to study the effect of important operating parameters such as mixing speed, temperature, reactant ratio and catalyst loading. The samples withdrawn were titrated for its total acid number (TAN) and the best condition to achieve highest conversion was attained. It was found that the mixing speed of 300rpm has minimised the external mass transfer resistances. Under the external diffusion-free regime, the maximum conversion, 96% was achieved at the temperature of 140oC, catalyst loading of 2.5wt% and reactant molar ratio of pelargonic acid to 2-ethylhexanol of 1:5. The bio-lubricant produced possessed the kinematic viscosity of 4.44 cSt at 40oC and 1.92 cSt at 100oC with a viscosity index of 366.247. The excellent viscosity properties are better than current commercial petro-lubricant and bio-lubricant available. However, the cloud point and pour point of 2-ethylhexyl pelargonate were observed at -18oC and -24 oC respectively which were still not in par with the commercial petro-lubricant although better than current bio-lubricant available. It is recommended that this work can be further studied by addition of additive e.g. antioxidant to enhance its lubrication properties and commercialised due to its high potential to replace petro-lubricant.